Chemical compositions and health promoting effects of edible mushrooms from genus Russula - Xinwen Hu; Baojun Xu (Elsevier, 2025)
Background: The genus Russula comprises a diverse range of edible mushrooms known for their remarkable health-promoting effects. Extensive research in the past two decades has delved into the bioactive compounds of Russula mushrooms, exploring their therapeutic potential. Purpose: This comprehensive review aims to examine the chemical diversity within the genus Russula and elucidate the contribution of these compounds to various health benefits, including antioxidant, antimicrobial, anticancer, immunoenhancing properties, observed in different Russula species. Study design: To ensure the reliability and comprehensiveness of the review, a systematic search was conducted on prominent databases such as Web of Science, Google Scholar, PubMed, Scopus, and ResearchGate to gather relevant data and insights from diverse scholarly sources. Methods: The review meticulously analyzed the nutritional constituents and phytochemical compositions of Russula mushrooms, focusing on their potential health-promoting effects. Results: The findings highlight the significant potential of Russula mushrooms in developing natural remedies for a wide range of health conditions, showcasing their diverse bioactive compounds and their associated benefits. Conclusion: Further research is warranted to uncover the underlying mechanisms of action and fully realize the clinical potential of Russula mushrooms in promoting human health and well-being.